Photocatalytic Decontamination of Sulfur Mustard Over Manganese Oxide Nanobelts. Issue 4 (26th December 2012) - Ramacharyulu, P.V.R.K.; Prasad, G.K.; Kumar, J. Praveen; Ganesan, K.; Singh, Beer; Dwivedi, K.
<x xml:space="preserve">Abstract</x> Photocatalytic decontamination of sulfur mustard was studied on manganese oxide nanobelts (MON) in the presence of Sun light and UV‐A light. Data obtained from the experiments conducted under the irradiation of Sun light and UV‐A light was compared with that of the obtained without irradiation of light. Sulfur mustard and the products of reaction were studied using gas chromatography, gas chromatography‐mass spectrometry techniques (GC‐MS). 100% of sulfur mustard was found to be decontaminated on the surface of MON with irradiation of Sun light in 8 h. Whereas without irradiation only 46% of sulfur mustard was found to be decontaminated. Superior Sun light activity of MON against sulfur mustard was attributed to its high irradiance. GC‐MS data indicated the formation of acetaldehyde, carbon dioxide, sulfur mustard sulfoxide, chloroethyl vinyl sulfide, and so forth, due to photocatalysis of sulfur mustard. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 1118–1123, 2013